1998
DOI: 10.1093/heapol/13.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Research report. The quality of private and public primary health care management of children with diarrhoea and acute respiratory infections in Tlaxcala, Mexico

Abstract: In Tlaxcala, Mexico, 80% of the children who died from diarrhoea or acute respiratory infections (ARI) in 1992-1993 received medical care; in more than 70% of cases it was provided by a private general practitioner (GP). The present study evaluated the quality of case management by private and public GPs to children under five years of age with diarrhoea and ARI. During the clinical observation, the treatment and counselling given to the mother were assessed with the WHO guidelines as reference standard. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…The study concluded that there is a need for intervention to curb the irrational use of antibiotics and injections in private clinics. A study from Mexico evaluated the quality of case management by private and public GPs to children under 5 years of age with diarrhoea and ARI (Bojalil et al, 1998). In the management of ARI, 66% and 58% of private GPs made a wrong decision in the prescription of antimicrobial and symptomatic drugs, respectively, compared with 30% and 20% of public GPs, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that there is a need for intervention to curb the irrational use of antibiotics and injections in private clinics. A study from Mexico evaluated the quality of case management by private and public GPs to children under 5 years of age with diarrhoea and ARI (Bojalil et al, 1998). In the management of ARI, 66% and 58% of private GPs made a wrong decision in the prescription of antimicrobial and symptomatic drugs, respectively, compared with 30% and 20% of public GPs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This de®nition gives a more medical therapeutic view of rational drug use and may substantially differ from the consumers' perspective. Unlimited access to and irrational use of drugs is common in many developing countries (Van der Geest, 1987;Some, 1994;Hossain et al, 1982;Alubo, 1994;Alam et al, 1998;Greenhalgh,there are two studies, one from Tanzania (Massele and Nsimba, 1997) and the other from Mexico (Bojalil et al, 1998), that have compared the differences among prescription practices of primary health care (PHC) providers working in the public and private sector.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the region have shown that more than half of the providers treating child diarrhoea cases and ARI are in the private sector (Berman and Rose, 1994); that private physicians account for 38% of the child treatment in rural areas of Guatemala (Van der Stuyft et al, 1996); and that in Mexico private practitioners perform significantly worse than public ones in terms of advice, therapy, and drugs prescribed for both diarrhoea and ARI (Bojalil et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the services provided in the Basic Health Services Package are designed to reduce the major causes of post-neonatal mortality such as child respiratory and intestinal infections, and malnutrition. Research, though limited, suggests that the quality of treatment for diarrheal diseases and respiratory infections was adequate in the public sector in Mexico prior to Progresa (Bojalil et al, 1998), so the interventions should be effective.…”
Section: Program Mechanisms To Reduce Infant and Neonatal Mortalitymentioning
confidence: 99%